2017
DOI: 10.1007/s11011-016-9948-1
|View full text |Cite
|
Sign up to set email alerts
|

Dietary adequacy of Egyptian children with autism spectrum disorder compared to healthy developing children

Abstract: Although the etiology and pathology of autism spectrum disorder (ASD) is still poorly understood, a number of environmental, anthropological, neurobiological and genetic factors have been related to the pathophysiology of ASD, even the impact of oxidative stress response related to the environment and nutrition intake. Usual recommended dietary habits are based on the combination of behavioral and dietary or nutraceutical interventions together with pharmacotherapy. Investigations about a reliable relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
3
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 52 publications
6
41
3
4
Order By: Relevance
“…The present study was undertaken to observe vitamin B 12 and folic acid status of ASD children.The mean serum vitamin B 12 and folic acid were significantly lower in ASD children compared to healthy control. Similar findings were reported by other investigators 13 . A cross sectional study on Egyptian children found significantly positive correlation between serum B 12 and folic acid with their food content.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study was undertaken to observe vitamin B 12 and folic acid status of ASD children.The mean serum vitamin B 12 and folic acid were significantly lower in ASD children compared to healthy control. Similar findings were reported by other investigators 13 . A cross sectional study on Egyptian children found significantly positive correlation between serum B 12 and folic acid with their food content.…”
Section: Discussionsupporting
confidence: 93%
“…A cross sectional study on Egyptian children found significantly positive correlation between serum B 12 and folic acid with their food content. They suggested nutritional deficiency was associated with autistic disorder in Egyptian children 13 .In this study, in addition to lower vitamin B 12 and folic acid level, 4% of ASD children were affected with vitamin B 12 deficiency whereas no control children had any deficiency of vitamin B 12 and folic acid . In the present study this observation further confirm to the association of low vitamin B 12 and folic acid to the current series of autistic children.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Although lower folate levels in pregnant women were associated with increased risk of ASD, the effects of folate‐enhancing interventions on the clinical symptoms of ASD have yet to be confirmed . As parents of autistic children are often concerned about the feeding behavior of their children, two studies have been conducted to determine the nutrients intake of autistic children . The findings showed that children with autism had significantly lower daily intake of folate, or folate plus vitamin B12, together with other types deficiencies of nutrients studied .…”
Section: Future Directionsmentioning
confidence: 99%
“…As parents of autistic children are often concerned about the feeding behavior of their children, two studies have been conducted to determine the nutrients intake of autistic children . The findings showed that children with autism had significantly lower daily intake of folate, or folate plus vitamin B12, together with other types deficiencies of nutrients studied . It is thereby important to ensure the adequate intake of folate through either diet or supplement for the benefit of reduction of other conditions, such as neural tube defects, which were found to be associated with folate deficiencies or hyperhomocysteinemia, even if it could have no effect in the improvement of clinical symptoms of ASD. Genes or pathways of the oxidative stress as a potential target: Some recent findings of increased red‐cell lipid peroxides, lipofuscin deposition, and urinary isoprostanes have been found in autistic children indicative of increase in oxidative stress in these children .…”
Section: Future Directionsmentioning
confidence: 99%